XIX. yüzyıl İstanbul şehir dokusunda saray kadınlarının etkisi - Şahin, Pınar (My University, 2021)
XIX. yüzyıl İstanbul’un kent dokusu açısından en büyük değişim yaşadığı asırdır. Reform hareketlerinin yoğunluk kazandığı bu dönemde devletin merkez teşkilatının batılı tarzda yeniden düzenlenmesi yanında şehircilik faaliyetleri açısından da birçok yeni düzenleme yapılmıştır. Toplumsal hayatın her alanını etkileyen bu süreçte Osmanlı saray kadınları baskın bir figür olarak karşımıza çıkmaktadır. Gerek şahsi birikimleri gerekse de devlet desteği ile inşa ve tamir ettirdikleri; dini, eğitim, askeri ve sivil yapılarla İstanbul şehir dokusunda kalıcı izler bırakmışlardır. Mevcut literatür yanında Osmanlı arşiv belgeleri ile desteklediğimiz bu çalışma ile saray kadınlarının XIX. yüzyıl İstanbul şehir dokusuna katkıları ortaya konulmuştur.

The 19th century was the century in which the urban fabric of Istanbul underwent its biggest transformation. During this period when the reform movement gained momentum, the state carried out western style restructuring and introduced many new city planning regulations. The important developments that took place after municipalities were established in 1855 consisted of building regulations put in place to facilitate significant changes to the city plan, and the coordination of residential areas and constructions. This process affected all spheres of society and the women of the Ottoman court emerged as a dominant force. Through their constructions and reconstructions of religious, educational, military and secular architecture using personal savings as well as state funding, the women left a lasting imprint on Istanbul’s urban fabric. In addition to the existing literature, in this study which we support with Ottoman archive documents, shows that urban fabric contributions were made the court women in 19th century Istanbul.
Keywords: Architecture; City planning; History; Istanbul; Istanbul (Turkey); Istanbul’s urban fabric; İstanbul; İstanbul (Türkiye); İstanbul şehir dokusu Ottoman Court women; Kadınlar; Kent planlama; Mimari; Osmanlı saray kadınları; Tarih; Turkey; Türkiye; Women